Location Estimation Using Space-Time Signal Processing in RFID Wireless Sensor Networks - Chang-Heon Oh (International Journal of Distributed Sensor Networks)
We consider real-time locating systems (RTLS) consisting of radio frequency identification (RFID) tags and multiantenna readers to propose a novel location estimation algorithm based on the concept of space-time signature matching for multipath environments. In contrast to previous fingerprint-based approaches that rely on received signal strength (RSS) information only, the proposed algorithm uses angle, delay, and RSS information from the received signal to form a signature, which in turn is utilized for location estimation. We evaluate the performance of the proposed algorithm in terms of the average error probability. Simulations and analytic results confirm the effectiveness of the proposed algorithm for location estimation even in non-line-of-sight (NLOS) environments.